Review of the Fund's Strategy on Overdue Financial Obligations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper provides an annual review of progress under the Fund's strengthened cooperative strategy on overdue financial obligations and proposes to extend the availability of the rights approach by another year, to end-August 2008. The rights approach could provide a useful mechanism for arrears clearance for the remaining eligible members, depending on their specific circumstances. A draft decision to this effect is provided in Section V.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Charge; Fund Resource; PP; The Fund; Sudan; Zimbabwe